ANALISIS KUALITAS PELAYANAN KESEHATAN TINGKAT PERTAMA TERHADAP KEPUASAN PASIEN PESERTA BPJS DI PUSKESMAS DONGI KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Nia Rahmadani; Andi Astinah Adnan; Sofyan B (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze the effect of primary healthcare service quality on the satisfaction of BPJS patients at Puskesmas Dongi. Service quality was measured using the five SERVQUAL dimensions: tangible, reliability, responsiveness, assurance, and empathy, while patient satisfaction was assessed based on patients’ perceptions of the services received. This research employed a quantitative approach with data collected through questionnaires. The population consisted of 632 BPJS patients, with a sample of 87 respondents determined using the Slovin formula. Data were analyzed using a Likert scale and processed with SPSS to determine the relationship between service quality and patient satisfaction. The results showed that the quality of healthcare services at Puskesmas Dongi was categorized as very good, with the average percentage score of each service dimension exceeding 80%. Facility cleanliness, service punctuality, and compliance with BPJS procedures were the most dominant indicators influencing patient satisfaction. In addition, the friendliness of healthcare staff and effective communication skills contributed to positive patient perceptions of the services provided. The study concludes that healthcare service quality has a positive effect on BPJS patient satisfaction. Therefore, continuous improvement in service quality, particularly in empathy and staff communication, is necessary to optimize healthcare services.